Electronic Signatures in Law - Mason, Stephen (Law Practitioner Series, 2012)
Electronic signatures are ubiquitous. Anyone sending an e-mail or using a credit card uses one. They can have a bearing on all areas of law, and no lawyer is immune from having to advise clients about their legal consequences. This third edition provides an exhaustive discussion of what constitutes an electronic signature, the forms an electronic signature can take and the issues relating to evidence, formation of contract and negligence in respect of electronic signatures. Case law from a wide range of common law and civil law jurisdictions is analysed to illustrate how judges have dealt with changes in technology in the past and how the law has adapted in response.